Mangalsutra alongside a Lakshmi Haar - Mumbai Archive Project Team (Jio Institute, 2024)
A woman adorns the mangalsutra alongside a Lakshmi Haar. The Lakshmi Haar, as its name implies, is a long necklace featuring circular designs embossed with the image of the Goddess Lakshmi, a symbol of wealth, fertility, and prosperity.